A rigorous computational model for hydrogen production from bio-ethanol to feed a fuel cell stack - Nieto Degliuomini, Lucas (2012)
A pseudo dynamic rigorous model of a bio-ethanol processor system (BPS) to produce hydrogen for feeding a Proton Exchange Membrane Fuel Cell (PEM-FC) is presented. The main contribution of this work is to give the overall set of differential and algebraic equations (DAE), assumptions and the way to computationally implement it. This model is able for testing the dynamic behavior of this integrated process, obtaining a reduced order Linear model and checking any plant-wide control structure design. It is implemented in two programs, HYSYS and MATLAB, properly communicated to coordinate the calculations performed on each one. A part of the process considered with a faster dynamic than the rest of the units of the plant are simulated in HYSYS environment working in steady state mode. Then, auxiliary equipments and the heat exchangers network are in HYSYS which is called by MATLAB every integration interval for doing the simulation of the complete SYSTEM. On the other side, the PEM-FC and the dynamic models of the plug flow reactors are developed in MATLAB workspace. Hence, strictly speaking this model must be considered as ?pseudo? dynamic. The linearized and reduced order model is developed by applying system identification techniques on the rigorous model. Therefore, accounting the main objectives of the process and the most critical disturbances, a preliminary control structure can be well-tested here. Several results are presented in this work analyzing the obtained performances for opened and closed loop modes.